The reality paradox: Authenticity, fidelity and the real in Battlefield 4. Issue 1 (1st October 2015) - Stevens, Richard; Raybould, Dave
This article examines how the 'Battlefield' (EA Games) series of games generates authenticity in its soundtrack both through a meticulous approach to modelling the physical world and through the appropriation of audio characteristics from our, typically mediated, experience of conflict. It goes on to examine how we might reconcile such 'authentic' audio with the more ludic features of the soundtrack, required to support gameplay, that are typically presented as inauthentic. The absence of these sounds during narrative-based sequences and the acceptance of them without negative impact on immersion during gameplay implies that these inauthentic sounds appear not to disrupt the immersive qualities of the 'authentic' but only when clearly positioned as ego-ludic (heard only by the player, non-spatialized and synthetic in quality) and only within the context of challenge-based sequences of the game.